Leukocyte profiles and body condition of free-living Burrowing owls (Athene cunicularia) from rural and urban areas - Cavalli, Matilde (2018)
Species living in urban areas are exposed to novel and potentially stressful human perturbations. In response to the increasing number of stressors in these habitats, animals may manifest changes in their immune system, body condition and physiology. Many bird species are negatively impacted by urbanization, but other species survive and thrive in urban areas. The capacity to adjust the stress responses to the conditions of urban areas may play a key role to explain the success of bird species in this habitat. In this study, we compared indicators of stress and body condition in free-living Burrowing owls (Athene cunicularia) inhabiting urban and rural areas. We calculated a scaled index of body condition, assessed leukocyte profiles and calculated the heterophil/lymphocyte (H/L) ratios of chicks and adult Burrowing owl individuals. We found that the total white blood cell counts, the relative leukocyte count, and the H/L ratio were similar in owls from rural and urban areas, as well as their body condition. Chicks showed higher counts of white blood cells relative to adult owls, which may be associated with developmental stages and immune system activation processes. Here we provide the first Burrowing owl baseline data of leukocyte profile, one that can be used as a reference when developing future studies.